Pengembangan Pembelajaran Berpikir Kritis-Kreatif Berbasis Blended Learning di SMA - A. H. Rofi'uddin; Gatut Susanto; Didin Widyartono; Sultan Sultan; Helmi Muzakki (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to develop a creative and critical learning model in which its effectiveness is tested in Bahasa Indonesia classes at the senior high school level. This study employed the Four D Thiagarajan method. The first stage is defined and completed by theoretical and empirical analysis. The theoretical analysis comprises the analysis of the related literature and previous studies. Meanwhile, the empirical analysis is done by analysing the problems, students’ characteristics, assignments, concepts, and the formulation of learning objectives. The second stage designs in which the learning model prototype is planned. The third stage is development, which includes developing and testing the prototype. The fourth stage is dissemination, in which the product is distributed. The final product is the syntax of the Bahasa Indonesia lesson in the senior high school level, which comprises 5M, namely ‘menstimulasi’ (to stimulate), ‘mengeksplorasi’ (to explore), ‘memberi respons’ (to give response), ‘memproduksi’ (to create), and ‘merefleksi’ (to reflect). Based on the testing, it is revealed that there is an increase in students’ scores of around 7.7 on a scale of 100. Therefore, it can be concluded that the creative and critical 5M learning is effective for implementation in Bahasa Indonesia classes at the senior high school level.